Alternative methods of seed potato (Solanum tuberosum) production: Indian perspective — a review (Current Horticulture, 2024)
Quality seed is a major and important input in potato cultivation. Due to vegetative propagation in potato, requirement of seed potato tubers is voluminous, accounting for 50 to 70% of the total cost of potato production. The productivity of potato in many countries is low, primarily due to either non-availability or inadequacy of quality seed potato. The alternative methods of seed potato production will not only help in bridging the gaps in demand but also assist in overcoming the problems that are inherently associated with the conventional multiplication system of potato. The information are meagre on these aspects.Therefore, an overview on seed potato and potato seed production via different alternative methods namely tuber sprout technique, synthetic seeds, true potato seeds, micro-propagation, bioreactor technology, hydroponic system, aeroponic system, techni tubers, apical rooted cuttings, little tubers and utilization of under-sized tubers (left in the field) is presented. Different aspects like, present scenario, significance, feasibility and practicability are being covered. Efforts that have been made to achieve a balance between use of quality seed potatoes via conventional and different alternative methods togethigher production and productivity of potato are covered here. Issues of higher occupancy of potato in cold storage space due to storage of conventional seed potatoes and how this can be reduced by enhancing the use of alternative methods with more effective and diversified utilization of cold storage space are also discussed.
Keywords: Aeroponics; Bio-reactor technology; Cold storage space; Hydroponics; Little-tubers; Micropropagation; Mini-tubers; Seed potato; Synthetic seeds